ACCUMULATIVE REPETITIVE STRAIN INJURY AMONG BUSINESS PROCESS OUTSOURCING EMPLOYEES: A SURVEY STUDY - Lamba, Dheeraj; Upadhyay, Ritambhara K (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Computer overuse syndrome or repetitive strain injury is the most common problem among the people in all age groups. Several studies have found the adverse effect of using computers for a long duration. In the modern tech-savvy world, usage of computers is something unavoidable. The objective of this survey study is to find out the accumulative repetitive strain injury among the business process outsourcing employees. Methods: This study was conducted in different business process outsourcings in Noida, and a convenient sampling method was used to collect data through Neck Pain Disability Index (NPDI) and disabilities of the arm, shoulder and hand (DASH) questionnaire. The study comprised of total 230 subjects. Results: The mean and standard deviation (SD) of NPDI score was found to be 32.12 and 11.26, respectively, whereas the mean and SD for DASH score was 24.34 and 7.44, respectively. The Chi-square value for NPDI and DASH was found to be 263.043 and 139.461. The study shows that upper extremity pain is a common problem in employees working in the IT sector. The employees showed high rates of computer useâ€“associated with upper extremity musculoskeletal symptoms and symptom-related functional limitation. Conclusion: The findings of the study suggest a need to begin to evaluate interventions and to reduce the risks of developing computer overuse syndrome such as developing upper extremity symptoms, disability, and disorders among employees working in the IT sector who use computers for more than 40 hrs/week. Intervention to reduce symptoms should include effective training in work rest patterns, good-working postures coupled with availability of appropriate equipment.